2, 4-Diamino-6-methylpyrimidines for the potential treatment of Chagas' disease. Issue 18 (1st October 2018) - Thomas, Michael G.; De Rycker, Manu; Cotillo Torrejon, Ignacio; Thomas, John; Riley, Jennifer; Spinks, Daniel; Read, Kevin D.; Miles, Tim J.; Gilbert, Ian H.; Wyatt, Paul G.
Graphical abstract: Highlights: Optimising selectivity and metabolic stability of anti-Chagas' disease pyrimidines. Structure activity relationships development to optimise developability properties. Development of compound not targeting T. cruzi C14 α-demethylase. Abstract: Chagas' disease, caused by the protozoan parasite Trypanosoma cruzi, affects 8–10 million people across the Latin American population and is responsible for around 12, 500 deaths per annum. The current frontline treatments, benznidazole and nifurtimox, are associated with side effects and lack efficacy in the chronic stage of the disease, leading to an urgent need for new treatments. A high throughput screening campaign against the physiologically relevant intracellular form of the parasite identified a series of 2, 4-diamino-6-methylpyrimidines. Demonstrating the series did not work through the anti-target Tc CYP51, and was generally cytocidal, confirmed its suitability for further development. This study reports the optimisation of selectivity and metabolic stability of the series and identification of a suitable lead for further optimisation.